Expertise in Second Language Learning and Teaching
XII, 258 p.
Keywords: Understanding what constitutes expertise in language learning and teaching is important for theoretical reasons related to psycholinguistic, and applied linguistic, enquiry. It also has many significant applications in practice, particularly in relation to the training and practice of language teachers and improvements in students' strategies of learning. In this volume, methodologies for establishing what constitutes expert practice are discussed and the contributions address the fields of listening, reading, writing, speaking and communication strategies, looking at common characteristics of the 'expert teacher' and the 'expert learner'.